Modulated QMF Filter Banks with Perfect Reconstruction - Malvar, Henrique S. (Electronics Letters, 1990)
Necessary and sufficient conditions for perfect reconstruction (PR) in a modulated filter bank are derived. It is shown that, for a bank of M filters of length L, PR can be obtained when L = 2KM, for any positive integer K, whereas previous results guaranteed PR only for K = 1.